High-temperature self-lubricating high-entropy rare earth boride ceramic material and preparation method thereof
Through the preparation of high-entropy rare earth boride ceramic materials, the wet ball mill mixing and sintering process of rare earth oxides and boron carbide powder is used to solve the problem of insufficient self-lubricating performance of high-temperature ceramic materials, and the excellent high-temperature self-lubricating performance in the range of 800~1200 ℃ is achieved, which is suitable for high-temperature friction and wear problems in high-end equipment mechanical systems.
Patent Information
- Application Number
- CN202411985281.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
It is difficult for existing high-temperature ceramic materials to achieve self-lubricating at high temperatures, and traditional liquid lubricants are prone to volatilization or oxidation failure at high temperatures, which cannot effectively solve the high-temperature friction and wear problems of high-end equipment mechanical systems.
High-entropy rare earth boride ceramic material is used to prepare high-entropy rare earth boride ceramic bulk materials with excellent high-temperature self-lubricating properties through wet ball milling mixing of rare earth oxides and boron carbide powder, pressurized solid phase reaction sintering and discharge plasma sintering processes.
The friction coefficient of this material in the range of 800~1200 ℃ is 0.10~0.24, which significantly improves the high-temperature self-lubricating performance and is suitable for high-temperature friction and wear problems in high-end equipment mechanical systems.
Smart Images

Figure CN119684008A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high entropy ceramics, and in particular to a high-temperature self-lubricating high entropy rare earth boride ceramic material and a preparation method thereof. Background Art
[0002] With the rapid development of cutting-edge technologies in my country such as aviation, aerospace, and nuclear power, the service conditions of mechanical moving parts in high-end equipment such as aircraft engines and hypersonic aircraft are becoming more and more demanding, and they are facing serious high-temperature friction and wear problems. Under extreme high-temperature conditions, traditional liquid lubricants are prone to volatilization or oxidation failure. Ceramic materials that can achieve high-temperature self-lubrication have good lubrication properties at high temperatures while maintaining high strength and hardness, which is suitable for solving high-temperature friction and wear problems in mechanical systems of high-end equipment.
[0003] High entropy rare earth boride ceramics have the characteristics of high melting point, high hardness, good electrical and thermal conductivity, excellent high temperature stability, etc., and have attracted extensive attention due to their unique physical, chemical and thermomechanical properties. Patent CN112408409 B discloses a (Y 1 / 5 Sm 1 / 5 Eu 1 / 5 Yb 1 / 5 Er 1 / 5 )B6 ceramic powder preparation method, and studied its wave absorbing properties, and obtained a high temperature resistant high entropy wave absorbing ceramic material. Patent CN 117700235 A discloses a method for preparing a high entropy rare earth boride ceramic material, and obtains a high entropy diboride containing a rare earth element (Sm or Lu or Er or Ho or Y or Tm) by adopting electric field sintering technology. Patent CN 119059824 A discloses a hexaboride RE (AE) containing both rare earth metal element RE and alkaline earth metal element AE x The preparation method of B6 and its optical properties were studied. The literature [J. Adv.Ceram, 2021, 10(1): 62-77] synthesized high-entropy rare earth hexaboride powder by a one-step method and studied its electromagnetic wave absorption performance. It is believed that REB6 ceramic material has good high-temperature stability, oxidation resistance and corrosion resistance. It is a new type of electromagnetic wave absorption material that can meet the requirements of high-temperature or corrosive service environments.
[0004] At present, the research on high-entropy rare earth boride ceramic materials is still in its infancy, and the research is mainly focused on the preparation of powder or porous materials. There is less research on dense block materials, especially the lack of research on tribological properties. In addition, by carrying out research on the preparation and performance of rare earth ceramic materials, promoting the multifunctional integrated development and diversified application of rare earth materials, it is helpful to promote the comprehensive utilization of my country's rare earth resources. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-temperature self-lubricating high-entropy rare earth boride ceramic material with excellent performance.
[0006] Another technical problem to be solved by the present invention is to provide a method for preparing the high-temperature self-lubricating high-entropy rare earth boride ceramic material.
[0007] To solve the above problems, the present invention discloses a high-temperature self-lubricating high-entropy rare earth boride ceramic material, characterized in that the ceramic material is in a block, has a friction coefficient of 0.10-0.24 at 800-1200 °C, and has the following chemical composition: REB6, wherein RE is selected from at least five of the lanthanide rare earth elements La, Nd, Sm, Eu, Gd, Dy, Ho, Yb, Sc and Y.
[0008] The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material as described above is characterized in that: the method refers to using RE2O3 powder and B4C powder as production raw materials, wherein the RE2O3 powder is at least five of La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, Ho2O3, Yb2O3 and Sc2O3 and Y2O3; firstly, the RE2O3 powder and the B4C powder are mixed uniformly by wet ball milling, and then dried and sieved through a 100-120 mesh sieve to obtain a mixed powder; after the mixed powder is sintered by a pressureless solid phase reaction, it is cooled to room temperature, ground and sieved through a 100-120 mesh sieve to obtain a high-entropy rare earth boride ceramic powder material; then the high-entropy rare earth boride ceramic powder material is subjected to spark plasma sintering to obtain a high-entropy rare earth boride ceramic block material.
[0009] The mass percentage of the RE2O3 powder is 60-70%, and the mass percentage of the B4C powder is 30-40%.
[0010] The purity of the RE2O3 powder is not less than 99.9%, and the particle size is 1-10 μm; the purity of the B4C powder is not less than 98%, and the particle size is 1-10 μm.
[0011] The conditions of the pressureless solid phase reaction sintering are a temperature of 1650-1800°C, a holding time of 1-3 h, a heating rate of 10-20°C / min, and a vacuum sintering atmosphere.
[0012] The conditions of the spark plasma sintering are as follows: the sintering temperature is 1750-1900°C, the holding time is 5-20min, the heating rate is 75-150°C / min, the sintering pressure is 25-35 MPa, and the sintering atmosphere is a vacuum or argon protective atmosphere.
[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention adopts a high-entropy material design concept and introduces rare earth elements. The material composition and performance can be adjusted in a large space, which can promote the multifunctional integrated development and diversified application of rare earth materials and help promote the comprehensive utilization of my country's rare earth resources.
[0014] 2. The present invention uses rare earth oxide and boron carbide powder as raw materials, and the raw material cost is low.
[0015] 3. The preparation process of the present invention is simple and has a short cycle, which is conducive to large-scale production.
[0016] 4. The high entropy rare earth boride ceramic block prepared by the present invention has excellent high-temperature self-lubricating performance through tribological performance testing, and the friction coefficient at 800-1200°C is 0.10-0.24. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0018] Figure 1 This is the XRD spectrum of the high entropy rare earth boride ceramic powder material synthesized by the reaction of the present invention.
[0019] Figure 2 This is the XRD spectrum and sintered sample of the high entropy rare earth boride ceramic block material of Example 3 of the present invention.
[0020] Figure 3 This is a friction coefficient-time curve of the high entropy rare earth boride ceramic block material of Example 3 of the present invention when rubbing against different matching materials at room temperature.
[0021] Figure 4 This is the friction coefficient-time curve of the high entropy rare earth boride ceramic block material at room temperature to 1200°C in Example 3 of the present invention. DETAILED DESCRIPTION
[0022] A high-temperature self-lubricating high-entropy rare earth boride ceramic material, which is in the form of a block and has a friction coefficient of 0.10-0.24 at 800-1200°C. It has the following chemical composition: REB6, wherein RE is selected from at least five of the lanthanide rare earth elements La, Nd, Sm, Eu, Gd, Dy, Ho, Yb, Sc and Y.
[0023] The preparation method of the high-temperature self-lubricating high-entropy rare earth boride ceramic material comprises the following steps: using RE2O3 powder and B4C powder as production raw materials, wherein the RE2O3 powder is at least five of La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, Ho2O3, Yb2O3, Sc2O3 and Y2O3; the purity of the RE2O3 powder is not less than 99.9%, and the particle size is 1-10 μm; the purity of the B4C powder is not less than 98%, and the particle size is 1-10 μm.
[0024] First, RE2O3 powder and B4C powder are mixed uniformly by wet ball milling, and the mass percentage (g / g) of RE2O3 powder is 60-70%, and the mass percentage (g / g) of B4C powder is 30-40%. After drying to constant weight at 60-80 °C, the mixed powder is passed through a 100-120 mesh sieve to obtain a mixed powder; the mixed powder is placed in a graphite crucible, and the graphite crucible is moved into a vacuum sintering furnace, and pressureless solid phase reaction sintering is carried out under the conditions of a temperature of 1650-1800 °C, a holding time of 1-3 h, a heating rate of 10-20 °C / min, and a vacuum sintering atmosphere. After cooling to room temperature, grinding, and passing through a 100-120 mesh sieve, a high entropy rare earth boride ceramic powder material (REB6 powder material) is obtained. Chemical reaction: RE2O3+3B4C→2REB6+3CO. Then the high entropy rare earth boride ceramic powder material is placed in a graphite mold and spark plasma sintered under the conditions of sintering temperature of 1750~1900 ℃, holding time of 5~20 min, heating rate of 75~150℃ / min, sintering pressure of 25~35 MPa, and sintering atmosphere of vacuum or argon protective atmosphere to obtain high entropy rare earth boride ceramic block material (REB6 block material).
[0025] Example 1 In terms of mass percentage (g / g), 8.8% Nd2O3, 15.5% Sm2O3, 13.7% Eu2O3, 13.1% Yb2O3, 13.9% Y2O3 rare earth oxide powders with a particle size of 5 μm and 35% B4C powder with a particle size of 5 μm were placed in a ball mill, and 20wt.% anhydrous ethanol was added as a wet ball milling medium. After ball milling, mixing, drying and sieving, a mixed powder was obtained; the mixed powder was placed in a graphite crucible, and the graphite crucible was moved into a vacuum sintering furnace for pressureless solid phase reaction sintering. The temperature was raised to 1650 ℃ at a heating rate of 10 ℃ / min, and the holding time was 3 h. The sintering atmosphere was vacuum. After the holding period, the mixture was cooled to room temperature with the furnace, and the high entropy rare earth boride ceramic powder material was obtained by grinding and sieving. The phase composition of the powder is as follows: Figure 1 As shown, the powder is mainly composed of REB6.
[0026] The high entropy rare earth boride ceramic powder material was placed in a graphite mold and sintered in a spark plasma furnace at a sintering temperature of 1900 ℃, a heating rate of 100 ℃ / min, and a sintering pressure of 25 MPa for 5 min to obtain a high entropy rare earth boride ceramic block material.
[0027] Example 2 Calculated by mass percentage (g / g), 9.3% Nd2O3, 16.1% Sm2O3, 14.4% Eu2O3, 13.9% Yb2O3, 14.3% Y2O3 rare earth oxide powders with a particle size of 1 μm and 32% B4C powder with a particle size of 10 μm were placed in a ball mill, and 20wt.% anhydrous ethanol was added as a wet ball milling medium. After ball milling, mixing, drying and sieving, a mixed powder was obtained; the mixed powder was placed in a graphite crucible, and the graphite crucible was moved into a vacuum sintering furnace for pressureless solid phase reaction sintering. The temperature was raised to 1750 ℃ at a heating rate of 15 ℃ / min, and the holding time was 2 h. The sintering atmosphere was vacuum. After the holding period, the mixture was cooled to room temperature with the furnace, and the high entropy rare earth boride ceramic powder material was obtained by grinding and sieving. The phase composition of the powder is as follows: Figure 1 As shown, there is almost no impurity peak and the powder purity is improved.
[0028] The high entropy rare earth boride ceramic powder material was placed in a graphite mold and sintered in a spark plasma furnace at a sintering temperature of 1800 ℃, a heating rate of 150 ℃ / min, and a sintering pressure of 30 MPa for 10 min to obtain a high entropy rare earth boride ceramic block material.
[0029] Example 3 In terms of mass percentage (g / g), 9.1% Nd2O3, 15.8% Sm2O3, 14.1% Eu2O3, 13.5% Yb2O3, 14.2% Y2O3 rare earth oxide powders with a particle size of 10 μm and 33.3% B4C powder with a particle size of 1 μm were placed in a ball mill, and 20wt.% anhydrous ethanol was added as a wet ball milling medium. After ball milling, mixing, drying and sieving, a mixed powder was obtained; the mixed powder was placed in a graphite crucible, and the graphite crucible was moved into a vacuum sintering furnace for pressureless solid phase reaction sintering. The temperature was raised to 1800°C at a heating rate of 20°C / min, and the holding time was 1 h. The sintering atmosphere was vacuum. After the holding period, the material was cooled to room temperature with the furnace, and the high entropy rare earth boride ceramic powder material was obtained by grinding and sieving. The phase composition of the powder is as follows: Figure 1 As shown, REB6 powder with high purity was obtained.
[0030] The high entropy rare earth boride ceramic powder material was placed in a graphite mold and sintered in a spark plasma furnace at a sintering temperature of 1750 °C, a heating rate of 75 °C / min, and a sintering pressure of 35 MPa for 15 min to obtain a high entropy rare earth boride ceramic block material. The phase composition of the block is as follows: Figure 2 As shown, it is consistent with the powder composition and maintains good phase stability during high temperature sintering.
[0031] The friction and wear properties of the prepared high-entropy rare earth boride ceramic block material in the atmospheric environment were evaluated using a GF-Ⅰ high-temperature reciprocating friction and wear tester: the friction pairs were Si3N4, Al2O3 and SiC ceramic balls, the friction load was 10 N, the amplitude was 5 mm, the frequency was 5 Hz, the test temperatures were room temperature, 800 ℃, 1000 ℃ and 1200 ℃, and the test time was 30 min. The test results are shown in Figure 3 and 4 At room temperature, when forming friction pairs with Si3N4, Al2O3 and SiC ceramic balls, they have a stable friction coefficient of about 0.50 ( Figure 3 ); When rubbing against Si3N4 ceramic ball, the friction coefficient at 800 ℃ is about 0.15, the friction coefficient at 1000 ℃ is reduced to 0.10, and it still has a low friction coefficient of about 0.24 at 1200 ℃. The experimental results show that the prepared high entropy rare earth boride ceramic block material has excellent high-temperature self-lubricating properties.
[0032] The above is an exemplary description of the embodiments of the present invention. However, any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims. The contents not described in detail in the specification of the present invention belong to the common technology of those skilled in the art.
Claims
1. A high-temperature self-lubricating high-entropy rare earth boride ceramic material, characterized in that: The ceramic material is in the form of a block, has a friction coefficient of 0.10-0.24 at 800-1200° C., and has the following chemical composition: REB6, wherein RE is selected from at least five of the lanthanide rare earth elements La, Nd, Sm, Eu, Gd, Dy, Ho, Yb, Sc and Y.
2. The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material according to claim 1, characterized in that: The method refers to using RE2O3 powder and B4C powder as production raw materials, wherein the RE2O3 powder is at least five of La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, Ho2O3, Yb2O3, Sc2O3 and Y2O3; firstly, the RE2O3 powder and the B4C powder are evenly mixed by wet ball milling, and then dried and passed through a 100-120 mesh sieve to obtain a mixed powder; after the mixed powder is sintered by a pressureless solid phase reaction, it is cooled to room temperature, ground and passed through a 100-120 mesh sieve to obtain a high-entropy rare earth boride ceramic powder material; then the high-entropy rare earth boride ceramic powder material is subjected to spark plasma sintering to obtain a high-entropy rare earth boride ceramic block material.
3. The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material according to claim 2, characterized in that: The mass percentage of the RE2O3 powder is 60-70%, and the mass percentage of the B4C powder is 30-40%.
4. The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material according to claim 2, characterized in that: The purity of the RE2O3 powder is not less than 99.9%, and the particle size is 1-10 μm; the purity of the B4C powder is not less than 98%, and the particle size is 1-10 μm.
5. The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material according to claim 2, characterized in that: The conditions of the pressureless solid phase reaction sintering are a temperature of 1650-1800°C, a holding time of 1-3 h, a heating rate of 10-20°C / min, and a vacuum sintering atmosphere.
6. The method for preparing a high-temperature self-lubricating high-entropy rare earth boride ceramic material according to claim 2, characterized in that: The conditions of the spark plasma sintering are that the sintering temperature is 1750-1900°C, the holding time is 5-20 min, the heating rate is 75-150°C / min, the sintering pressure is 25-35 MPa, and the sintering atmosphere is a vacuum or argon protective atmosphere.
Citation Information
Patent Citations
Porous high-entropy hexaboride ceramic and preparation method thereof
CN110615681A
High-entropy rare earth co-doped nano low-heat-transfer powder material and preparation method thereof
CN114524440A
A high-hardness, self-lubricating, single-phase, high-entropy ceramic material and its preparation method
CN114933478A
Preparation method of high-entropy high-strength wear-resistant ceramic material and application of high-entropy high-strength wear-resistant ceramic material in dental restoration
CN115417675A
High-temperature friction self-adaptive single-phase self-lubricating high-entropy ceramic and preparation method thereof
CN117383943A